Photochemical Oxidation of Dimethyl Sulphoxide by Singlet Oxygen - Mali, S.L.; Vaidya, Veena; Pitliya, R.L.; Vaidya, V.K.; C. Ameta, Suresh (Asian Journal of Chemistry, 2010)
Reaction of dimethyl sulphoxide with singlet oxygen was carried out using methanol as a solvent in presence of a sensitizer rose bengal. A white solid product was isolated and characterized as dimethyl sulphone by physical, chemical and spectral methods. A quantitative mechanism has been proposed for this reaction.